Early assessment of the efficacy of noninvasive ventilation tested by HACOR score to avoid delayed intubation in patients with moderate to severe ARDS. (February 2022) - Bai, Linfu; Ding, Fei; Xiong, Weiming; Shu, Weiwei; Jiang, Lei; Liu, Yuliang; Duan, Jun
Background: Use of noninvasive ventilation (NIV) in patients with moderate to severe ARDS is controversial. We aimed to use HACOR (combination of heart rate, acidosis, consciousness, oxygenation and respiratory rate) score to comprehensively assess the efficacy of NIV in ARDS patients with PaO2 /FiO2 ⩽ 150 mmHg. Methods: Secondary analysis was performed using the data collected from two databases. We screened the ARDS patients who used NIV as a first-line therapy. Patients with PaO2 /FiO2 ⩽ 150 mmHg were enrolled. NIV failure was defined as requirement of intubation. Results: A total of 224 moderate to severe ARDS patients who used NIV as a first-line therapy were enrolled. Of them, 125 patients (56%) experienced NIV failure and received intubation. Among the intubated patients, the survivor had shorter time from initiation of NIV to intubation than nonsurvivors (median 10 vs 22 h, p < 0.01). The median differences of HACOR score before and 1–2 h of NIV were 1 point (interquartile range: 0–3). We defined the patients with △HACOR >1 as responders (n = 102) and the rest to non-responders (n = 122). Compared to non-responders, the responders had higher HACOR score before NIV. However, the HACOR score was lower in the responders than non-responders after 1–2 h, 12 h, and 24 h of NIV. The responders also had lower NIV failure rate (36% vs 72%, p < 0.01) and lower 28-day mortality (32% vs 47%, p = 0.04) than non-responders. Conclusions: NIV failure was high among patients with moderate to severe ARDS. Delayed intubation is associated with increased mortality. The reduction of HACOR score after 1–2 h of NIV can identify the patients who respond well to NIV.